Genetic Research Practices with Marginalized Communities: A Case for Responsive Justice - Goering, Sara (The Hastings Center report, 2008)
Genetics researchers often work with distinct communities. To take moral account of how their research affects these communities, they need a richer conception of justice and they need to make those communities equal participants in decision-making about how the research is conducted and what is produced and published out of it.